2009
DOI: 10.1002/jbio.200810070
|View full text |Cite
|
Sign up to set email alerts
|

The potential for histological screening using a combination of rapid Raman mapping and principal component analysis

Abstract: Rapid Raman mapping was carried out on 20 microm sections of oesophageal biopsy samples. Contiguous 7 microm sections were stained with haematoxylin and eosin (H&E) with histopathology provided by an expert pathologist. The step size and acquisition times were varied and the resulting spectra, principal component (PC) score maps and loads were compared. Overall mapping times were also compared to traditional Raman point mapping. The principal component loads for each of the maps were seen to be similar despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 31 publications
1
54
0
Order By: Relevance
“…a Raman map. Recent studies have demonstrated mapping of fresh tissue sections using unsupervised multivariate analysis methods such as K-means (KM) clustering analysis [5][6][7][8][9], hierarchical cluster analysis (HCA) [6] and principal component analysis (PCA) [10]. However there are no published studies to date that apply Raman mapping approaches to de-paraffinized tissue.…”
Section: Biophotonicsmentioning
confidence: 98%
“…a Raman map. Recent studies have demonstrated mapping of fresh tissue sections using unsupervised multivariate analysis methods such as K-means (KM) clustering analysis [5][6][7][8][9], hierarchical cluster analysis (HCA) [6] and principal component analysis (PCA) [10]. However there are no published studies to date that apply Raman mapping approaches to de-paraffinized tissue.…”
Section: Biophotonicsmentioning
confidence: 98%
“…Additionally, curve fitting was used in these studies to detect the changes in the main peaks' intensity in relation to a reference peak. Recently, principal component analysis was shown to improve dramatically the signal-to-noise ratio of noisy spectra from large data sets [Hutchings et al, 2009], but becomes computationally impractical if the data set is too large. However, due to the direct relationship between the solution of k-mean clustering and principal component analysis [Ding and He, 2004], k-mean clustering offered the same level of analytical power of a large data set but with vastly superior computational speed.…”
Section: Discussionmentioning
confidence: 99%
“…9,24 In addition, similar efforts using Raman spectroscopy, another form of vibrational spectroscopy, have yielded analogous results. [25][26][27][28] These studies mostly were aimed at demonstrating that vibrational (IR and Raman) spectroscopy can detect spectral differences between normal tissue types, and between normal and diseased tissue. However, the data sets were generally restricted in size such that rigorous statistical validation was impossible, or used data analysis procedures that were not completely objective.…”
mentioning
confidence: 99%